Development of Guided Inquiry-Based Chemical Handout in Buffer Solution Materials for Senior High School - Ardianto Ardianto; Susilawati Susilawati; Rasmiwetti Rasmiwetti (Journal of Educational Sciences, 2019)
This research is motivated by the still limited teaching materials or learning tools that facilitate students in enriching experiences, developing knowledge and activeness of students, and supporting students to formulate their own discoveries. The limitations of these learning tools will certainly affect the quality of learning, especially in chemistry learning. The purpose of this study is to develop a guided inquiry-based chemical handout on a valid buffer solution based on aspects of content suitability, language worthiness, presentation worthiness and graphic worthiness. The research design used research and development design with a 4-D development model. The 4-D development model has four stages: Define, Design, Develop, and Disseminate. This research was carried out until the development stage and followed by limited trials. Data collection techniques was in the form of validation sheets and questionnaire responses of teachers and students. Data analysis technique used descriptive analysis. The results show an average percentage rating of three experts at 93% with a valid category. The results of trials to teachers and students each obtained an average percentage score of 94% and 86%. From the results of the study it can be concluded that the guided inquiry-based chemical handout on buffer solution material for SMA is valid and good for a learning handout.